A blanket against darkness : a collection of stories - Harton, Catherine, 1983- (Literary translation collection., 2019)
"In forests where ancestors know the fine powder of snow raised by the wind as the breath of death, a woman makes jewellery from the feathers of birds, a 54-year-old man corresponds with the author of a message in a bottle cast into the sea, another waits, mouth open towards the heavens, to drink his fill from a thunderstorm looming on the horizon. Nature breathes anew in this book where forgiveness is offered and asked for. A Blanket Against Darkness is ripe with talismans from the earth. Its landscapes remind us that we are of the north and that we are not alone in the world. We live in places populated with relics, where a single abrupt movement may cause the migration of an entire settlement. Published by Marchand de Feuilles in 2015, Traité des peaux was a finalist for both the Governor General's Literary Award for novels and short stories and the Prix des Cinq continents de la Francophonie."--